2003
DOI: 10.1073/pnas.0535708100
|View full text |Cite
|
Sign up to set email alerts
|

An agonist-induced switch in G protein coupling of the gonadotropin-releasing hormone receptor regulates pulsatile neuropeptide secretion

Abstract: The pulsatile secretion of gonadotropin-releasing hormone (GnRH) from normal and immortalized hypothalamic GnRH neurons is highly calcium-dependent and is stimulated by cAMP. It is also influenced by agonist activation of the endogenous GnRH receptor (GnRH-R), which couples to Gq/11 as indicated by release of membrane-bound ␣q/11 subunits and increased inositol phosphate͞Ca 2؉ signaling. Conversely, GnRH antagonists increase membrane-associated ␣q/11 subunits and abolish pulsatile GnRH secretion. GnRH also sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 50 publications
5
103
1
2
Order By: Relevance
“…Antiproliferative signaling of GnRH in human reproductive tract tumors is mediated through the PTX-sensitive G i protein (43,44). Moreover, recent research has demonstrated that, in GT1 cells, GnRH-modulated neuronal Ca 2ϩ signaling occurs also via G i inhibitory mechanisms (45). Our findings in human olfactory neurons suggest that GnRH, according to its concentration, is able to switch the coupling of GnRH-R to specific G proteins and thus to regulate distinct biological responses (46).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Antiproliferative signaling of GnRH in human reproductive tract tumors is mediated through the PTX-sensitive G i protein (43,44). Moreover, recent research has demonstrated that, in GT1 cells, GnRH-modulated neuronal Ca 2ϩ signaling occurs also via G i inhibitory mechanisms (45). Our findings in human olfactory neurons suggest that GnRH, according to its concentration, is able to switch the coupling of GnRH-R to specific G proteins and thus to regulate distinct biological responses (46).…”
Section: Discussionmentioning
confidence: 62%
“…A specific GnRH receptor antagonist blocked the migratory promoting activity of GnRH. Moreover, the fact that PTX pretreatment was able to reduce GnRH-dependent migration in a dose-dependent manner suggests that these effects were coupled to PTX-sensitive G i/o proteins (43)(44)(45). Several factors, including anosmin-1 (48), NELF (3), the receptor tyrosine kinase Ark (11), and FGFR1 (20), have been described as playing a role in some aspects of GnRH cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…In various cell types, the GnRHR has been shown to regulate G␣ s , G␣ q/11 , and G␣ i/o family G proteins (17)(18)(19)(20)(21)(22)(23)(24). To guide the study of G protein coding of gonadotropin expression, we determined which G protein mRNAs were expressed in gonadotrope cells.…”
Section: G Protein Expression In Gonadotropes-mentioning
confidence: 99%
“…On the other hand, in reproductive tumor cells, G␣ i/o played an important role in GnRHR signaling by regulating MAPK activation and in inhibiting cell proliferation in response to GnRH stimulation (20 -23). In the GnRH-producing neurons of the hypothalamus, G␣ i and G␣ q were involved in the pulsatile GnRH release in response to autocrine/paracrine GnRH stimulation (24). G protein activation by GnRHR may vary, as the GnRHR-activated G protein shifted from G␣ s to G␣ i under increasing GnRH concentration in hypothalamic neurons (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation